Análisis y diseño de una solución cloud como servidor alterno al data center e implementación de un prototipo de infraestructura para el GADMUR - Logacho Lincango, John Leonardo (2016)
This project is focused on the analysis and design of a Cloud solution, which serves as a backup for the data center of the Gobierno Autonomo Descentralizado Municipal de Rumiñahui, paying attention that the cloud computing service is one technological tool that gradually have been introduced in the world of ICT "Information and Communications Technology." GADMUR is an organization of local government and public service, which is committed to improve constantly some processes to satisfy of users and community. For this reason, it seeks to start using Cloud Computing, taking as a contingency plan, which objectives main of services, information that contain are not affected if they suffer a disaster in their infrastructure. For this reason, it has been considered a depth analysis and design of the best solution or alternative, based on Cloud technology, which provides services stored on virtual servers that are accessed through a private or public network. Finally, the contribution of this study in general, is providing an alternative for the information protection through the cloud, as well as, the implementation of a prototype, which allows a view of the positive and negative aspects, that lead the adoption of this service.